Paths to Global Health: the World Health Organization's Role in Confronting COVID-19 Challenges - Dinamika, Kevin Ramadhani (Jurnal Transformasi Global, 2023)
Abstract This study aims to analyze the role played by WHO as a world health institution in overcoming the COVID-19 pandemic. Using the concept of Global Health Governance and Reordering Health to Health Security from Annmarie Bindenagel ehović, this study wants to see changes in the arrangement of health as a vital aspect and agreed by all countries. The findings in this study showing that WHO has made significant changes to the global health order aspects in stages as seen from the way WHO has handled pandemics and epidemics that occurred before COVID-19. However, from the research  there is founding that WHO's siding with one country, which is an obstacle according to other countries. Keywords: COVID – 19, Pandemic, WHO, China, Global Health Governance